Pengaruh Profitabilitas, Likuiditas Dan Leverage Dalam Memprediksi Financial Distress Di Masa Mendatang - Purwanti Purwanti; Juwita Larasati Puspita Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Financial distress has an impact on the financial performance of a company, which can cause bankruptcy for the company, so efforts are needed for the company to prevent this from happening. This study raises the topic of financial distress with the aim of finding out whether the selected independent variables have an influence on financial distress, namely profitability on financial distress, liquidity on financial distress, and leverage on financial distress, and also whether together profitability, liquidity, and leverage affect financial distress. In this research, the proportional sampling method was used in selecting the sample with secondary data as the sample data. The findings obtained from this research are that a high liquidity ratio causes an increase in the company's financial distress. Keywords: Profitability; Liquidity; Leverage; Financial Distress